2022
DOI: 10.1007/s10560-022-00833-9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the impact of COVID-19 on stress and Access to Services for Licensed and Kinship Caregivers and Youth in Foster Care

Abstract: Children in foster care in the United States face unique challenges related to access to health and education services. With the COVID-19 pandemic, many of those services were temporarily disrupted, adding burden to an already strained system. This observational study describes the experiences of licensed and kinship caregivers (N = 186) during the peak of COVID-19 stay-at-home orders and as restrictions to services were lifted, to understand the overall impact of COVID-19 on this already vulnerable population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Garcia et al (2015) found that kinship caregivers were more depressed compared with their foster care counterparts. However, kin children experienced significantly lower internalizing problems with caregivers within the “never depressed category.” Similar to populations at large that have seen increasing demand and limited availability for mental health care in recent years, Beal et al (2022) reported that about half of caregivers in this study experienced barriers to accessing mental health services during the pandemic.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…Garcia et al (2015) found that kinship caregivers were more depressed compared with their foster care counterparts. However, kin children experienced significantly lower internalizing problems with caregivers within the “never depressed category.” Similar to populations at large that have seen increasing demand and limited availability for mental health care in recent years, Beal et al (2022) reported that about half of caregivers in this study experienced barriers to accessing mental health services during the pandemic.…”
Section: Resultssupporting
confidence: 56%
“…Similar to other parenting populations, resilience to these negative outcomes is also occurring, especially when caregivers have structural supports (Huang et al, 2019). In addition to the varying mental and physical health challenges faced by kin caregivers, barriers to mental health resources remain prevalent for this population (Beal et al, 2022; Garcia et al, 2015). Higher incomes were found to be positively correlated with improved caregiver well-being (Gomez, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of the articles in this issue dealt with macro-level or policy issues. Beal (2022) examined the impact of COVID-19 on stress and access to services, comparing licensed foster parents and kinship caregivers. As Beal and colleagues pointed out, much of the literature comparing licensed foster parents and kinship caregivers has highlighted the differences between these two groups in terms of economic resources, social support, and eligibility for assistance programs.…”
Section: Policy and Macro-level Implications Of Foster Caregiving And...mentioning
confidence: 99%
“…For example, Lipien et al ( 2022 ) interviewed caseworkers in child welfare services to examine their perspectives on educational experiences among youth in foster care during COVID-19 and discovered that youth in foster care had some difficulties with engaging in learning due to a lack of in-person tutoring and resources (e.g., online learning tools) as well as distractions. Similarly, another recent study of educational challenges facing youth in foster care revealed that most of the youth in foster care did not complete four or more hours of education per day (Beal et al, 2022 ), and foster parents had issues making adjustments for online learning (Whitt-Woosley et al, 2022 ).…”
Section: Educational Challenges Among Youth In Foster Carementioning
confidence: 99%